Excellent Ultracold Molecular Candidates From Group VA Hydrides: Whether Do Nearby Electronic States Interfere? - Li, Donghui; Bian, Wensheng (Frontiers in Chemistry, 2021)
By means of highly accurate ab initio calculations, we identify two excellent ultracold molecular candidates from group VA hydrides. We find that NH and PH are suitable for the production of ultracold molecules, and the feasibility and advantage of two laser cooling schemes are demonstrated, which involve different spin-orbit states (A3Π2 and X3Σ1− ). The internally contracted multireference configuration interaction method is applied in calculations of the six low-lying Λ-S states of NH and PH with the spin-orbit coupling effects included, and excellent agreement is achieved between the computed and experimental spectroscopic data. We find that the locations of crossing point between the A3Π and Σ−5 states of NH and PH are higher than the corresponding v′ = 2 vibrational levels of the A3Π state indicating that the crossings with higher electronic states would not affect laser cooling. Meanwhile, the extremely small vibrational branching loss ratios of the A3Π2 → a1Δ2 transition for NH and PH (NH: 1.81 × 10–8; PH: 1.08 × 10–6) indicate that the a1Δ2 intermediate electronic state will not interfere with the laser cooling. Consequently, we construct feasible laser-cooling schemes for NH and PH using three lasers based on the A3Π2 → X3Σ1− transition, which feature highly diagonal vibrational branching ratio R00 (NH: 0.9952; PH: 0.9977), the large number of scattered photons (NH: 1.04×105; PH: 8.32×106) and very short radiative lifetimes (NH: 474 ns; PH: 526 ns). Our work suggests that feasible laser-cooling schemes could be established for a molecular system with extra electronic states close to those chosen for laser-cooling.